Experiments with Realism in Irish Language Short Stories by Daithí Ó Muirí - de Brún, Sorcha (Hungarian Journal of English and American Studies, 2020)
Relying on Joseph McMinn’s statement that the connection between realist and non-realist fiction is not a hierarchical relationship, this essay maintains that realism in Irish language fiction is, and has always been, an energizing force for experimentation. This is nowhere more evident than in the work of writer Daithí Ó Muirí (1954-), a native English speaker now residing in an Irish speaking area in Ireland. Much of Ó Muirí’s work is experimental due to his use of allegory and fantasy, yet many of the stories remain rooted in the realities of the world, particularly in his representations of masculinities and in works concerning the impact of war, violence, and displacement on men’s lives. The essay examines Ó Muirí’s first three collections, Seacht Lá na Díleann (1998), Cogaí (2002), and Uaigheanna agus Scéalta Eile (2002), in which he explores subjects that are classically realistic: war, death, religion, and relationships between men and women. The essay explores how Ó Muirí’s work often combines realism and magic realism, and shows that Ó Muirí’s fiction provides a fresh if somewhat bleak narrative of 21st century realism in Irish language prose fiction.